A Comparison of Macro‐Level Sustainability Indices for OECD Countries: Conceptual and Measurement Issues1. Issue 2 (June 2014) - Engelbrecht, Hans‐Jürgen
<x xml:space="preserve">Abstract</x> The paper contributes to the debate about how to empirically assess sustainability using the capital approach to development. It focuses on OECD countries for which intangible capital makes up a very large proportion of total wealth. After discussing growth rates of GDP per capita, total wealth per capita and its main subcategories over the 1995–2005 period, correlations between different monetary sustainability indices associated with the capital approach are explored. The conceptually preferred index "change in total wealth per capita" that includes intangible capital is only weakly correlated with the other indices. The analysis is extended to also include some prominent non‐monetary composite sustainability indices. This strengthens the earlier findings. The main message of the paper is that if we accept change in total wealth per capita as the preferred measure, commonly used adjusted net savings‐based indices might be quite misleading, at least for OECD countries.